Synthesis of lithium titanium oxide (Li4Ti5O12) with ultrathin carbon layer using supercritical fluids for anode materials in lithium batteries - Hong, Seung-Ah; Lee, Sue Bin; Joo, Oh-Sim; Kang, Jeong Won; Cho, Byung-Won; Lim, Jong-Sung (SPRINGER, 2016)
Lithium titanium oxide (LTO: Li4Ti5O12) particles were produced via a continuous supercritical fluid process for use as anodes in lithium ion batteries. The synthesized LTO particles in supercritical water (scH(2)O) or in supercritical methanol (scMeOH) generate nanoparticles of 10-30 nm sizes, and the modified LTO particles using oleylamine in scMeOH affects the inhibition of particle growth. The modified LTO particle was coated by the usage of supercritical carbon dioxide (scCO(2)) and polyethylene glycol (PEG-400). The conformal coverage of the carbon layer on LTO particles with a thickness of 1.2 nm, and a uniform distribution of carbon on the entire surface of LTO particles are confirmed. The modified and carbon-coated LTO with a carbon content of 5.3 wt% exhibits a high discharge capacity of 175 mAh/g (which approaches the theoretical value of LTO) at 0.1 C and 83 mAh/g at 50 C. The carbon-coated LTO prepared using supercritical fluids delivered 160, 153, 123 mAh/g at 1 C and 60 A degrees C, room temperature, and -25 A degrees C, respectively.
Keywords: TEMPLATE-FREE SYNTHESIS; ELECTROCHEMICAL PERFORMANCE; NANOSTRUCTURED MATERIALS; NEGATIVE ELECTRODE; COATED LI4TI5O12; FACILE SYNTHESIS; NICKEL FILMS; NANOPARTICLES; METHANOL; STORAGE